1970
DOI: 10.3329/jdmc.v18i1.6313
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy with a Normal live Foetus and a Partial Molar Placenta - An Extremely Rare Condition

Abstract: The incidence of a normal live foetus along with a partial molar placenta is extremely rare. Although triploidy is the most frequent association, a foetus with normal karyotype can survive in cases of partial molar pregnancy. A case is reported in the Department of Obstetrics & Gynaecology, Dhaka Medical College Hospital, Dhaka that of partial molar placenta in which a live male baby was delivered at 34 weeks gestation by a 25 years old woman. At the 23rd week, ultrasonographic examination revealed a norma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…After the delivery, it is mandatory to check the patient until there have been 12 consecutive months of negative hCG levels. In conclusion, in every case of molar pregnancy suspect for a normal fetus, adequate counseling of the patient and a strict follow-up during and after pregnancy for the risk of persistence of the trophoblastic pathology are necessary [1820].…”
Section: Resultsmentioning
confidence: 99%
“…After the delivery, it is mandatory to check the patient until there have been 12 consecutive months of negative hCG levels. In conclusion, in every case of molar pregnancy suspect for a normal fetus, adequate counseling of the patient and a strict follow-up during and after pregnancy for the risk of persistence of the trophoblastic pathology are necessary [1820].…”
Section: Resultsmentioning
confidence: 99%
“…A chorionic villous biopsy could be done if a live fetus is present, to confirm the diagnosis and to differentiate between a partial mole and complete mole: it has been reported that the latter has approximately 20% tendency to become an invasive mole or even a choriocarcinoma, while the risk was lower for partial moles (14,16). Follow-up BhCG during and following pregnancy in order to early identify cases of persistent trophoblastic disease, invasive mole and choriocarcinoma is necessary (17)(18)(19).…”
Section: Discussionmentioning
confidence: 99%
“…Some factors may influence survival of fetus in PHM: (1) normal karyotype of fetus, (2) smaller size of grape tissue of placenta, (3) the rate of molar degeneration, (4) nonanemia state of fetus, and (5) the absence of maternal complications such as preeclampsia, thyrotoxicosis, and profuse vaginal bleeding 12 . Our case described some of these factors, such as diploid karyotype, few and focal extent of hydatidiform tissue of placenta, low rate of molar degeneration, and the absence of fetal anemia.…”
Section: Discussionmentioning
confidence: 99%